2016
DOI: 10.3390/ijerph13060614
|View full text |Cite
|
Sign up to set email alerts
|

Wayfinding the Live 5-2-1-0 Initiative—At the Intersection between Systems Thinking and Community-Based Childhood Obesity Prevention

Abstract: Childhood obesity is complex and requires a ‘systems approach’ that collectively engages across multiple community settings. Sustainable Childhood Obesity Prevention through Community Engagement (SCOPE) has implemented Live 5-2-1-0—a multi-sector, multi-component childhood obesity prevention initiative informed by systems thinking and participatory research via an innovative knowledge translation (KT) model (RE-FRAME). This paper describes the protocol for implementing and evaluating RE-FRAME in two ‘existing’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Examples from Three Thematic CI Areas Thematically, most of the reviewed articles consisted of CI initiatives related to (1) children's nutrition, food, and obesity. For example, enhancing healthy eating and breastfeeding, healthy food consumption, obesity reduction, and assessing the impacts of nutrition-related CI initiatives provided the primary focus for the majority of the reviewed CI initiatives (Amed et al 2015(Amed et al , 2016Blake-Lamb et al 2018;Bonnevie et al 2020;Grumbach et al 2017;Leruth et al 2017;Hermann et al 2017;Meinen et al 2016). All CI initiatives related to food and nutrition, except for one which dealt with breastfeeding promotion (Leruth et al 2017), covered multiple regions, and included local partners.…”
Section: Multiregional and Local Partnerships And Their Their Backbonmentioning
confidence: 99%
“…Examples from Three Thematic CI Areas Thematically, most of the reviewed articles consisted of CI initiatives related to (1) children's nutrition, food, and obesity. For example, enhancing healthy eating and breastfeeding, healthy food consumption, obesity reduction, and assessing the impacts of nutrition-related CI initiatives provided the primary focus for the majority of the reviewed CI initiatives (Amed et al 2015(Amed et al , 2016Blake-Lamb et al 2018;Bonnevie et al 2020;Grumbach et al 2017;Leruth et al 2017;Hermann et al 2017;Meinen et al 2016). All CI initiatives related to food and nutrition, except for one which dealt with breastfeeding promotion (Leruth et al 2017), covered multiple regions, and included local partners.…”
Section: Multiregional and Local Partnerships And Their Their Backbonmentioning
confidence: 99%
“…Generalizable methodologies focus on scientifically rigorous evaluation of complex community change initiatives that enhance their relevance for policy makers and/or funders to extend to other contexts (Amed et al, 2016;Komro et al, 2016;Lee & Chavis, 2012;Peters et al, 2016). Stepped Wedge Cluster Ran dom Control Trials, longitudinal studies with standardized continuous measure ment, interrupted time-series designs, multiple baseline designs, and cost-benefi t analysis were all identified as scientifically rigorous evaluation strategies for CCIs utilizing a range of quantitative data from cluster detection to socio-economic in dicators, asset mapping, and spatial patterning, as well as qualitative data through questionnaires and semi-structured interviews (Kingsley et al, 2014;Komro et al, 2016).…”
Section: Evaluation Methodologiesmentioning
confidence: 99%
“…Who determines relevance and credibility, and what are the appropriate crite ria for such determinations? ( Abboud & Claussen, 2016;Amed, Shea, Pinkney, Wharf Higgins, & Naylor, 2016;Cabaj, 2014;Cook, 2015;Coombe, 2012;Fiester, 2011;Kania & Kramer, 2011) A related debate concerned scientific rigour. Developmental methodologies view internal validity as key to enabling contextual learning, connecting eff orts to outcomes within specific contexts (Bradford & Chouinard, 2009).…”
Section: Debates In Evaluation Of Ccismentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also found that community involvement in research was an effective element. [33][34][35] The existence of active communities was a key element of local systems, enabled where needed by community development, social action and support for grassroots approaches and community asset transfer (ii. Active communities).…”
Section: Involving Communitiesmentioning
confidence: 99%